CRR/CRD IV: the trees and the forest - Masera, Rainer (PSL Quarterly Review, 2014)
This paper offers a review of the new CRR/CRD IV capital regulatory framework for banks in the EU, which represents the transposition into European law of the Basel III standard. Major shortcomings of the Second Capital Accord are examined, and the repair work is assessed in the light of the recognised need to amend the flaws. It is argued that the necessary adjustments must be evaluated in the holistic framework provided by the Banking Union approach. The main features of the new system are reviewed as components of an interconnected, complex network. The critical analysis highlights the significant improvements with respect to the Basel II standard, but it also brings to the fore the weaknesses which continue to characterise the new capital regulatory framework. Keywords: capital regulation, Basel III, risk, Banking Union, Modigliani-Miller JEL Codes: G01, G13, G21, G28